Tubular overexpression of transforming growth factor-β1 induces autophagy and fibrosis but not mesenchymal transition of renal epithelial cells - Koesters, Robert; Kaissling, Brigitte; LeHir, Michel; Picard, Nicolas; Theilig, Franziska; Gebhardt, Rolf; Glick, Adam B.; Hähnel, Brunhilde; Hosser, Hiltraud; Gröne, Hermann-Josef; Kriz, Wilhelm (The American journal of pathology, 2010)
We recently showed in a tetracycline-controlled transgenic mouse model that overexpression of transforming growth factor (TGF)-β1 in renal tubules induces widespread peritubular fibrosis and focal degeneration of nephrons. In the present study we have analyzed the mechanisms underlying these phenomena.
Gesehen am 21.03.2023